Video Production and Youth-Educator Collaboration: Openings and dilemmas - Stack, Michelle (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractThis study explores a collaborative project between high school youth and adult educators (graduate students in education) to create public service announcements. How do young people and educators talk about media, politics, power, and social change? Based on my observations of participant interaction, I argue that power is not dichotomous, with adults necessarily exerting power over youth. The very act of creating a collaborative video can provide a meaningful pedagogical tool to mobilize the individuals involved to engage in conversations about the meaning of social justice and strategies for achieving greater social justice.